Gods, Gays, and Guns: Religion and the Future of Democracy - Sekou, Osagyefo Uhuru (Chalice Press, 2018)
Cover -- Acclaim for first edition of God, Gays, and Guns -- Copyright -- Contents -- Prologue: Worshiping Whiteness -- Vocation of Agony -- Whose God? -- Speaking in Tongues -- Whoâs Going to Directthe Choir? -- Gays Are the New Niggers -- Queering Democracy and Christianity -- What Meaneth This? -- Dear God, from Haiti -- An Elegy for Innocence -- Back cover